Dimensional adjectives in Croatian: the interplay of semantic, cognitive and structural factors - Stanojević, Mateusz-Milan; Tuđman Vuković, Nina (2009)
Most traditional (Bierwisch 1970) and cognitive (Vogel 2004) analyses of dimensional adjectives (e.g. deep, shallow, thick, thin, wide, narrow) focus on their non-metaphorical senses. Moreover, spatial uses of pairs like deepshallow are frequently cited as prime examples of antonyms. This paper is an investigation into the complete semantic structure of the Croatian dimensional adjectives dubok ‘ deep’ and plitak ‘ shallow’ , taking into consideration their spatial (cf. a) and abstract (cf. b) uses: (a) Na tom je mjestu Bosut relativno plitak. ‘ At this location the river Bosut is relatively shallow.’ (b) Posljedica toga je duboki revolt i ogorcenost. ‘ The consequence of this is deep revolt and bitterness.’ We propose a usage-based framework combining semantic, cognitive and structural factors. More specifically, we explore 1) how oppositeness of meaning is realized with respect to different senses of dubok ‘ deep’ and plitak ‘ shallow’ , i.e. whether antonymy operates only on the level of their spatial meaning or whether it extends to other senses ; 2) what are the form-meaning correlations with reference to the predicative and attributive uses of both adjectives (assuming that the syntactic patterns will reflect conceptual differences), and 3) which sense functions as central, in light of the frequency of pattern – conceptual entrenchment debate. The data was extracted from the Croatian National Corpus. Dubok ‘ deep’ exhibits a more elaborate semantic structure with more distinct senses than the adjective plitak ‘ shallow’ . Consequently, their oppositeness of meaning is asymmetrical, being confined primarily to the spatial sense and less so to understanding and cognition senses (e.g. dubok/plitak dijalog ‘ deep/shallow dialogue’ ), confirming that antonymy is a matter of construal (Cruse – Togia 1995). The adjectives exhibit clear form-meaning patterns: metaphorical uses of both dubok and plitak are predominantly attributive with values of 60% or more, while the spatial sense shows an equal distribution of attributive and predicative uses. Attributiveness may be related to the essential properties of the modified nouns, while predicative uses may refer to properties that are not intrinsic to the concepts described, but indicate one of the two extreme points on the deep-shallow scale. Antonymy of the spatial sense is thus reflected in the usage patterns, as is the existence of predominantly attributive uses of metaphorical senses of one adjective that in principle do not have their counterparts in the other adjective. The most frequent sense of dubok is the abstract sense ‘ strong, difficult to change’ (over 40% of examples ; cf. (b) above), while the most frequent sense of plitak is the spatial sense describing the vertical dimension of a container with downward direction (60% of all examples ; cf. (a) above). We argue that, contrary to the frequency – entrenchment correlation proposed by the usage-based model of language (Kemmer – Barlow 2000), other factors like embodiment play a decisive role in determining the central or prototypical sense. This is confirmed by an elicitation test given to 200 hundred native speakers of Croatian, whose responses unambiguously point to the cognitive centrality and entrenchment of the spatial sense, indicating ‘ container and/or fluid contents’ as the typical referent noun. References Bierwisch, M. (1967). Some semantic universals of German adjectivals. Foundations of Language, 3, pp. 1– 36. Cruse, D. A. – Togia, P. (1995). Towards a cognitive model of antonymy. Lexicology, 1, pp. 113– 141. Kemmer, S. – Barlow, M. (2000). Introduction: A usage-based conception of language. In: Barlow, M. – Kemmer, S. (eds.) Usage-based Models of Language. Stanford: CSLI Publications, pp. vii– xxviii. Vogel, A. (2004). Swedish Dimensional Adjectives. Acta Universitatis Stockholmiensis. Stockholm: Almqvist & Wiksell International.
Projekt MZOS
ENG